2008
DOI: 10.1242/dev.018044
|View full text |Cite
|
Sign up to set email alerts
|

Indian hedgehog signals independently of PTHrP to promote chondrocyte hypertrophy

Abstract: Chondrocyte hypertrophy is an essential process required for endochondral bone formation. Proper regulation of chondrocyte hypertrophy is also required in postnatal cartilage homeostasis. Indian hedgehog (Ihh) and PTHrP signaling play crucial roles in regulating the onset of chondrocyte hypertrophy by forming a negative feedback loop, in which Ihh signaling regulates chondrocyte hypertrophy by controlling PTHrP expression. To understand whether there is a PTHrP-independent role of Ihh signaling in regulating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
211
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(221 citation statements)
references
References 26 publications
10
211
0
Order By: Relevance
“…Interestingly, during OA, articular chondrocytes undergo phenotypic and gene expression changes that recapitulate normal growth plate chondrocyte development 6 . Moreover, Hh signaling is important in the post-natal maintenance of articular cartilage and trabecular bone 69,93,95 . I hypothesize that, during OA, Hh signaling is dysregulated in articular cartilage.…”
Section: Animal Models Of Oamentioning
confidence: 99%
“…Interestingly, during OA, articular chondrocytes undergo phenotypic and gene expression changes that recapitulate normal growth plate chondrocyte development 6 . Moreover, Hh signaling is important in the post-natal maintenance of articular cartilage and trabecular bone 69,93,95 . I hypothesize that, during OA, Hh signaling is dysregulated in articular cartilage.…”
Section: Animal Models Of Oamentioning
confidence: 99%
“…In long bone development, it has been previously reported that BMP signaling in the cartilage may mediate the effect of Ihh (Mak et al, 2008) and that Ihh is a direct target of the BMP pathway (Retting et al, 2009). Given the established role of the BMP pathway during cranial suture formation (Warren et al, 2003), we decided to examine the possible relationship between Ihh and Bmp in the suture mesenchyme and calvarial bones.…”
Section: Loss Of Ihh In the Developing Calvaria Negatively Affects Bmmentioning
confidence: 99%
“…These findings suggest that Ihh and PTHrP function in a negative feedback system during latestage chondrocyte development. Recently, it has also been shown that Ihh stimulates chondrocyte maturation and calcification in a PTHrP-independent manner (Kobayashi et al, 2005;Amano et al, 2008;Mak et al, 2008). These results indicate that the precise role of the PTHrP/Ihh negative feedback loop is more complicated than initially proposed and that the regulation of PTHrP expression is complex.…”
Section: Introductionmentioning
confidence: 96%